THE USE OF DIDACTIC GAMES AS A MEANS OF INCREASING THE EFFECTIVENESS OF CHEMISTRY EDUCATION (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
The article presents an algorithm for compiling a didactic game, methodological recommendations for their organization and implementation in the process of teaching chemistry to students of grades 8-9. The effectiveness of systematic and purposeful application of didactic games in teaching secondary school students has been experimentally proven.